EFEITO AGUDO DOS EXERCÍCIOS PRIMORDIAIS NAS RESPOSTAS CARDIORESPIRATÓRIAS, AFETIVAS E DOR LOMBAR DE GESTANTES DE RISCO HABITUAL: ENSAIO CLÍNICO RANDOMIZADO - Renata Barbosa Balle Guimaraes (2023)
Introduction: Most international guidelines have recommended aerobic exercise for pregnant women in order to prevent non-transmissible chronic diseases and improve quality of life during pregnancy. However, training with resistance exercise is still scarce in the literature. Objective: to compare the acute effect of the exercise protocol with primordial movements on pain in high-risk pregnant women, comparing its results with those of a walking session. Method: Clinical trial of the acute type composed of 26 pregnant women, aged between 25 and 39 years in the period between the 2nd and 3rd gestational trimester. The volunteers participated in the following moments: (a) familiarization, (b) execution of the proposed protocol with primordial movements, (c) execution of the walking protocol. Each session lasted an average of 45 minutes. The subjective perceived effort was used before the sessions to guide the pregnant women. Cardiorespiratory responses such as systolic and diastolic blood pressure, heart rate, respiratory rate, oxygen saturation were recorded before and after each experimental session; the Visual Analogue Scale was used to assess pain intensity before and after the sessions. The Feeling Scale and the Physical Activity Enjoyment Scale were used after the sessions. Results: there was no effect of time, treatment or interaction between the two variables for the dependent variables systolic and diastolic diastolic blood pressure, heart rate, respiratory rate, and oxygen saturation; at the time after treatment, the Visual Analogue Scale score was lower for primordial movements than for walking; regarding the feelings and pleasure scales, at the moment after the treatment, the scores for both scales were higher after the primordial movements, when compared with those after the walk. For data evaluation, the two-way ANOVA test of repetitive measures was used, followed by Tukey's post-test and the paired t de Student. Statistical analysis was performed using the SigmaPlot statistical program, version 12.0, considering a significance level of 5%. Conclusion: the primordial movements protocol does not significantly interfere with the physiological cardiorespiratory responses systolic and diastolic blood pressure, heart rate, respiratory rate, and oxygen saturation, being safe for the practice of pregnant women; promotes reduction of lumbar pain and is a more pleasurable modality than walking.